Tanycytes As Regulators of Seasonal Cycles in Neuroendocrine Function - Lewis, Jo E.; Ebling, Francis J. P. (Frontiers in Neurology, 2017)
Annual cycles of physiology and behavior are highly prevalent in organisms inhabiting temperate and polar regions. Examples in mammals include changes in appetite and body fat composition, hibernation and torpor, growth of antlers, pelage and horns, and seasonal reproduction. The timing of these seasonal cycles reflects an interaction of changing environmental signals, such as daylength, and intrinsic rhythmic processes: circannual clocks. As neuroendocrine signals underlie these rhythmic processes, the focus of most mechanistic studies has been on neuronal systems in the hypothalamus. Recent studies also implicate the pituitary stalk (pars tuberalis) and hypothalamic tanycytes as key pathways in seasonal timing. The pars tuberalis expresses a high density of melatonin receptors, so is highly responsive to changes in the nocturnal secretion of melatonin from the pineal gland as photoperiod changes across the year. The pars tuberalis in turn regulates tanycyte function in the adjacent hypothalamus via paracrine signals. Tanycytes are radial glial cells that persist into adulthood and function as a stem cell niche. Their cell soma are embedded in the ependymal lining of the third ventricle, and they also send elaborate projections through the arcuate nucleus, many of which terminate on capillaries in the median eminence. This anatomy underlies their function as sensors of nutrients in the circulation, and as regulators of transport of hormones and metabolites into the hypothalamus. In situ hybridization studies reveal robust seasonal changes in gene expression in tanycytes, for example, those controlling transport and metabolism of thyroid hormone and retinoic acid. These hormonal signals play a key role in the initial development of the brain, and experimental manipulation of thyroid hormone availability in the adult hypothalamus can accelerate or block seasonal cyclicity in sheep and Siberian hamsters. We hypothesize that seasonal rhythms depends upon reuse of developmental mechanisms in the adult hypothalamus and that tanycytes are key orchestrators of these processes.